2021
DOI: 10.1371/journal.pone.0247090
|View full text |Cite
|
Sign up to set email alerts
|

Clinical benefit for clinical sequencing using cancer panel testing

Abstract: Background Clinical sequencing using a panel of genes has recently been applied worldwide for patients with refractory solid tumors, but the significance of clinical sequencing using gene panel testing remains uncertain. Here we sought to clarify the feasibility and utility of clinical sequencing in the treatment of refractory tumors at our hospital. Methods A total of 39 patients with advanced solid tumors treated at our hospital between 2018 and 2020 were enrolled in the clinical sequencing. Among them, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
(61 reference statements)
0
2
0
Order By: Relevance
“…Currently, multi-CGP testing is applied to patients with advanced solid tumors who fail to respond to standard therapies in Japan (13). Some reports indicate that cancer genome tests should be performed before first-line treatment (14)(15)(16). Our study indicated that multi-CGP testing may help in the early examination, which will increase opportunities for "precision cancer care" based on genetic variants because cancer gene profiling testing takes time to finalize reports.…”
Section: Discussionmentioning
confidence: 72%
“…Currently, multi-CGP testing is applied to patients with advanced solid tumors who fail to respond to standard therapies in Japan (13). Some reports indicate that cancer genome tests should be performed before first-line treatment (14)(15)(16). Our study indicated that multi-CGP testing may help in the early examination, which will increase opportunities for "precision cancer care" based on genetic variants because cancer gene profiling testing takes time to finalize reports.…”
Section: Discussionmentioning
confidence: 72%
“…Gene expression arrays (used in melanoma classifications) [ 61 ], and next-generation sequencing (NGS) are helping physicians determine how patients will respond to a particular therapy. These arrays and NGS will advance gene profiling technology to develop patient-specific treatments [ 62 , 63 ]. PM is very effective in treating some types of brain tumors, such as glioblastoma [ 64 ], using photodynamic therapy (PDT) [ 65 ].…”
Section: Introductionmentioning
confidence: 99%